Managing the oncologic patient with suspected pneumonia in the intensive care unit. Issue 10 (2nd October 2016) - Leoni, D.; Encina, B.; Rello, J.
ABSTRACT: Introduction : Solid cancer patients are frequently admitted in intensive care units for critical events. Improving survival rates in this setting is considered an achievable goal today. Respiratory failure is the main reason for admission, representing a primary target for research. Areas covered : This review presents a diagnostic and therapeutic algorithm for pneumonia and other severe respiratory events in the solid cancer population. It aims to increase awareness of the risk factors and the different etiologies in this changing scenario in which neutropenia no longer seems to be a decisive factor in poor outcome. Bacterial pneumonia is the leading cause, but opportunistic diseases and non-infectious etiologies, especially unexpected adverse effects of radiation, biological drugs and monoclonal antibodies, are becoming increasingly frequent. Options for respiratory support and diagnostics are discussed and indications for antibiotics in the management of pneumonia are detailed. Expert commentary : Prompt initiation of critical care to facilitate optimal decision-making in the management of respiratory failure, early etiological assessment and appropriate antibiotic therapy are cornerstones in management of severe pneumonia in oncologic patients.